Effects of anabolic androgenic steroids on mice ovarian and the possible protective role of ascorbic acid - Mohammed, H A; Okail, H. A (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Testone - E (TE) is an anabolic androgenic steroids (AAS) and widely used as a medical drug which possesses multiple clinical therapeutic benefits. The aim of this study was to determine the effects of TE on the ovarian tissue of adult female mice and the possible protective role of ascorbic acid (AA).